Tracing developmental changes in L2 learners’ structuring of phrasal verbs: a corpus study of native and non-native argumentative essays - Sung, Min-Chang; Kim, Hyunwoo (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study investigates the production patterns of English phrasal verbs (PV) by Korean-speaking foreign language learners of English, with a special focus placed on two structural features of PVs, namely, transitivity and particle placement. It offers a developmental perspective by analysing the production performance of PVs for three learner corpora at different proficiency levels (basic, intermediate, and advanced) and a native corpus. The results show that, while the basic- and intermediate-level learners significantly underused both transitive and intransitive PVs compared to the native speakers, the proportions of transitive and intransitive PVs in the advanced-learner corpus were statistically indistinguishable from those in the native corpus. In addition, verbparticle separation was identified only in the advanced-leaner and native corpora, indicating the specific developmental aspects underlying the L2 acquisition of PVs. The advanced learners, however, were found to be less capable of adhering to the end-weight principle and the givenness condition when structuring transitive PVs compared to the native speakers. These results suggest that associating contextual information with PV structures may be a major source of difficulty when teaching and learning PVs.